Extra Corporial Shock Wave Lithotripsy Sulaimani Teaching Hospital - Rasheed, Aso Omar (Sulaimani Journal for Pure and Applied Sciences, 2001)
A total of 70 patients with urinary stone disease had ESWL therapy in sulaimania teaching hospital .Disigne; this is a prospective study on a recent available trestment Clinical assessment were made by post ESWL therapy when the patients pass the gravels and followed by a series of radiological examinations for the success of the therapy results; tie study showed a success rate of 77% patients required up to 3 months to achieve stone free . Conclusion; ESWL provide a non invasive,simple therapy for the management of urinary stone disease, provided the stone is less than 2cm.
Keywords: Extracorporialshock wave; Renal stone; Ureteric stone